2014
DOI: 10.9790/0853-131125356
|View full text |Cite
|
Sign up to set email alerts
|

Demographic,Histopathological Patterns and Clinical profile of Oral Squamous Cell Carcinoma (OSCC) at a tertiary level referral Hospital in Vidarbha ( Central India) : A 7-year Retrospective Study

Abstract: Oral cancers are one of the leading cancers in the world.However ,in India,it is one of the most common cancer and a major public health problem.The purpose of this study was to evaluate retrospectively the demographics,histopathological and clinical profile of patients with oral cancer reported at a tertiary level referral hospital in Central India.A total of 908 biopsy proven OSCC cases were retrospectively analyzed and data was collected for a period of 7 years from January 2007 to December 2013 with refere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
5
2
0
Order By: Relevance
“…In line with this, the mean age for OSCCs was 55 years in our study, an age group considered as a risk group of OC (Zini, Czerninski, & Sgan‐Cohen, ). This result is in accordance with several other studies from different demographic groups (Alves et al, ; Malhotra et al, ).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In line with this, the mean age for OSCCs was 55 years in our study, an age group considered as a risk group of OC (Zini, Czerninski, & Sgan‐Cohen, ). This result is in accordance with several other studies from different demographic groups (Alves et al, ; Malhotra et al, ).…”
Section: Discussionsupporting
confidence: 94%
“…OSCC was more frequent in males than in females, similar to a recent report by GLOBOCAN (IARC, ) and studies from the neighboring country India (Malhotra et al, ; Salian, Dinakar, Shetty, & Ajila, ). The higher number of OSCCs among males might be related to higher percentage of males using tobacco products (betel quid and tobacco chewing) and alcohol than women, as suggested by previous reports (Lee et al, ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…21,22 In our study 76% cases were above the age of 40 years and males were predominant (74%). Similar findings were observed by Malhotra et al, 23 Shyam Sunder et al 24 and Doshi Neena et al 25 Tobacco addiction group consisted 92.30% males and only 7.70% females. High proportion of cases among males may be due to tobacco consumption in them.…”
Section: Discussionsupporting
confidence: 86%
“…Gender difference though present, with the male population being 69.7%, no statistically significant difference was observed. A higher predominance OSCC in male was in accordance with studies reported by Ayala et al [11] and Malhotra et al [12] In contrast, Harshani et al [13] reported a higher female predominance.…”
Section: Discussionsupporting
confidence: 90%